PROPOSALS TO IMPLEMENTATION OF ENVIRONMENTAL TAXES IN THE TRIBUTARY SYSTEM, AIMED AT ASSIST IN THE PRESERVATION OF THE ENVIRONMENT IN PERU - Valencia Gutiérrez, Adolfo (2010)
The establishment of taxes, designed to assist in the preservation of the environment is a strategic choice for environmental management through the performance of duty to contribute and the polluter pays principle, both fall within the principle of solidarity. Our goal is to show that environmental taxes have a clearly a tax. Thus, the technical coordination of environmental taxation must meet the principles of justice that inform the duty to contribute, as they are on track. The design of environmental taxation, within the boundaries set by those principles, ensures it flows into the calm sea of constitutional justice. Also, the overflow is the cause for the rule of law legal tax catastrophe: it unconstitutional. That is why we fulfill our social responsibility to propose the urgent implementation of environmental taxes to preserve the environment in Peru.